The association between maternal diabetes and neonatal seizures: a nested case–Control study - Liang, Yanjin; Liu, Juman; Lin, Xianbin (Frontiers in Pediatrics, 2023)
Aim: To evaluate the association of pre-gestational diabetes mellitus (PGDM) and gestational diabetes mellitus (GDM) with neonatal seizures during neonatal hospitalization. Methods: In this nested case-control study, all data came from National Vital Statistics System (NVSS) 2016-2021 data files. Considering the effect of confounders, we used propensity-score matching (PSM, case: control=1:4) method to select the study population. The outcome was considered as the occurrence of neonatal seizures. Univariate and multivariate logistic regression analyses were adopted to assess the association of PGDM and GDM with neonatal seizures. We also conducted stratified analyses according to gestational age, birthweight, Apgar score and maternal age, to explore the potential disparities. Results: After using PSM method, a total of 6,674 cases of neonatal seizures and 26,696 controls were included. After adjusting covariates, PGDM was associated with an increased risk of neonatal seizures [odds ratio (OR)=1.51, 95% confidence interval (CI): 1.15-1.98], whereas the association between GDM and neonatal seizures is not statistically significant. Additionally, the correlation of PGDM and increased risk of neonatal seizures was observed in neonates with a gestational age of 37-42 weeks and ≥42 weeks, with an Apgar score of ≥7 and with a maternal age of ≤40 years. Conclusion: PGDM was found to be closely associated with an increased risk of neonatal seizures. The findings of our study indicated that neonatologists should consider monitoring the incidence of neonatal seizures in neonates born to mothers with PGDM.